Exploring research data in Indian institutional repositories. Issue 2 (2014) - Mohammad Hanief Bhat
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to explore various types of research materials in Indian institutional repositories. Design/methodology/approach – The repositories are identified from the Registry of Open Access Repositories (ROAR). The repository sites were visited to collect the data necessary for the study. Findings – The present study reveals that barring a few repositories the collections of most of the repositories are very low. The percentage of archived materials is high for journal papers, and moderate for conference papers/thesis. However it is very low for preprints/working papers, teaching resources and patents. Originality/value – The study provides an overview of archived material in institutional repositories in India. <ack> <x xml:space="preserve"> Acknowledgements </x> The author is highly grateful to the Editor and the referees for their helpful comments in editing this paper. </ack>